Household contact investigation for the detection of tuberculosis in Vietnam: economic evaluation of a cluster-randomised trial - Thomas Lung, PhD; Guy B Marks, PhD; Nguyen Viet Nhung, PhD; Nguyen Thu Anh, PhD; Nghiem Le Phuong Hoa, MSc; Le Thi Ngoc Anh, BSc; Nguyen Binh Hoa, PhD; Warwick John Britton, PhD; Jessica Bestrashniy, PhD; Stephen Jan, PhD; Gregory J Fox, PhD (Elsevier, 2019)
Summary: Background: Active case finding is recommended as an important strategy to control tuberculosis, particularly in low-income and middle-income countries with a high prevalence of the disease. However, the costs and cost-effectiveness of active case finding are unclear due to the absence of evidence from randomised trials. We assessed the costs and cost-effectiveness of an active case finding strategy in Vietnam, where there is a high prevalence of tuberculosis. Methods: We conducted an economic evaluation alongside the Active Case Finding in Tuberculosis (ACT2) trial-a pragmatic cluster-randomised controlled trial in 70 districts across eight provinces of Vietnam. Patients aged 15 years and older with smear-positive pulmonary tuberculosis were recruited to the trial if they lived with one or more other household members. Household contacts were verbally invited to the clinic by the index patient with tuberculosis. ACT2 compared a combination of active and passive case finding with usual care (passive case finding) of household contacts of patients with tuberculosis from a health system perspective. Clustering occurred at the district and household level. Districts were the unit of randomisation, and we used minimisation to ensure balance of intervention and control districts within each province. In the intervention group, participants were invited to attend screening at baseline, 6 months, 12 months, and 24 months. We determined health-care costs with a standardised national costing survey and reported results in 2017 $US. The primary outcome of our study was disability-adjusted life years (DALYs) averted over a 24-month period. ACT2 was registered prospectively with the Australian and New Zealand Clinical Trials Registry, number ACTRN126.100.00600044. Findings: Between Aug 11, 2010, and Aug 11, 2015, 10 964 index patients and 25 707 household contacts completed the ACT2 study. There were 10 069 household contacts in the intervention group and 15 638 household contacts in the control group. The incremental cost-effectiveness ratio per DALY averted was $544 (330-1375). Interpretation: Active case finding was shown to be highly cost-effective in a setting with a high prevalence of tuberculosis. Investment in the wide-scale implementation of this programme in Vietnam should be strongly supported. Funding: Australian National Health and Medical Research Council.